INTERPROFESSIONAL SKILLS DEVELOPMENT IN PUBLIC HEALTH EDUCATION TO ADDRESS ONE HEALTH PROBLEMS - JojolaMount, Valerie (My University, 2020)
To investigate interprofessional practice (IPP) within the Kansas State University environment, I conducted analysis of surveys completed by undergraduate, professional, and graduate students, to better understand what communication skills—if any—were emphasized during the course of educational attainment. The study included the generation of a pre-test, IPP-related scenarios for analysis by participants, and creation of a post-test. The overall purpose was to understand if these skills are incorporated into public health, veterinary medicine, and One Health curricula at the graduate and professional levels and address potential gaps in this knowledge base in undergraduate contexts. With multiple disciplinary work being the way of the future, the skills provided within training modules like this are invaluable and should be underscored for all students, even in undergraduate educational attainment. Moreover, this study demonstrates the potential effectiveness of IPP work in an online, asynchronous format—further easing the possible time and location constraints typically associated with this kind of training.
Keywords: interprofessional practice; communication; education; One Health